Typical Culinary as Brand Image of Samarinda - Lanang Nala, I Wayan; Indriani, Novita (Stupa, 2020)
This study aims to identify the typical culinary of Samarinda in order to support the tourism destination branding from the gastronomic tourism point of view. This study used descriptive qualitative method where data collected form advance literature of local culinary history. Questionnaire also used to gather public perceptions about culinary branding of Samarinda. Data collected were then analyzed using the concept of Gastronomic Tourism. The research foud that types of culinaries considered to become the identity of a typical Samarinda culinary brand using the concept of Gastronomic Tourism are Nasi Kuning and Nasi Bekepor. These two culinary specialties are the most chosen by respondents where 56% of respondents mentioned Nasi Kuning while 24% mentioned Nasi Bekepor. According to triangle concept of gastronomic tourism, these two culinary products fulfill the elements of Food, Culture and History. It is also expected that these culinary products would be able to influence on brand positioning and brand image of Samarinda and also as a bridge for the buying interest of tourists visiting Samarinda.